Effect of approximation of curvature/inertia on the nonlinear vibrations of cantilever beam. (August 2020) - Kumar, Ajay
Abstract: The nonlinear dynamic response of cantilever beams under transverse harmonic excitation is investigated experimentally and numerically. The experimental set up, finite element formulation with accurate representation of curvature/inertia nonlinearities, multi-modal transverse displacement approximation and solution methodology for the periodic solution of the resulting nonlinear equations of motion are described. The experimental and numerical results of nonlinear periodic response are compared and the detailed study is carried out to investigate the effects of approximation of curvature/inertia nonlinearities and transverse displacement on the nature/degree of nonlinearity.